CROSS SECTIONAL STUDY OF DEPRESSION, ANXIETY AND QUALITY OF LIFE IN GLAUCOMA PATIENTS AT A TERTIARY CARE CENTRE. - Mandal, Govind Kumar; Roy, Pummy; Choudhary, Jagdish (Student's Journal of Health Research Africa, 2024)
Background The chronic nature Glaucoma, along with the apprehension of blindness and ongoing treatment, may render patients susceptible to depression and anxiety, sometimes overlooked in therapeutic environments. Objective To investigate the prevalence and severity of depression and anxiety, as well as their impact on quality of life in patients diagnosed with glaucoma at a tertiary care centre. Methods This cross-sectional observational study was performed for a duration of 12 months at Jawahar Lal Nehru Medical College and Hospital, Bhagalpur. One hundred ten patients diagnosed with primary open-angle or angle-closure glaucoma were enrolled following informed consent. Standardized tools, such as the Hospital Anxiety and Depression Scale (HADS) and the National Eye Institute Visual Function Questionnaire-25 (NEI VFQ-25), were utilized to assess psychological condition and vision-related quality of life (QoL). Demographic and clinical characteristics, including age, gender, glaucoma type and duration, visual acuity, and intraocular pressure, were documented. Results Among the 110 participants, 42.7% displayed signs of depression, while 38.1% experienced clinically significant anxiety. Depression was more common in patients with advanced-stage glaucoma and bilateral visual field impairment. The NEI VFQ-25 scores were markedly diminished in individuals exhibiting elevated HADS scores, signifying a robust correlation between impaired visual function and compromised mental health and quality of life. Female patients and individuals with prolonged disease duration exhibited markedly elevated anxiety scores (p < 0.05). Conclusion Depression and anxiety are prevalent yet frequently disregarded comorbidities in glaucoma patients, significantly affecting their quality of life. Recommendation Routine psychological assessment and comprehensive mental health assistance should be incorporated into glaucoma therapy techniques, especially for patients with advanced illness, bilateral involvement, and unfavorable visual outcomes. A multidisciplinary strategy incorporating psychological counseling may enhance overall patient well-being and adherence to treatment.